North American avian species that migrate in flocks show greater long-term non-breeding range shift rates - Stephen H. Vickers; Timothy D. Meehan; Nicole L. Michel; Aldina M. A. Franco; James J. Gilroy (Movement Ecology)
Abstract Background Many species are exhibiting range shifts associated with anthropogenic change. For migratory species, colonisation of new areas can require novel migratory programmes that facilitate navigation between independently-shifting seasonal ranges. Therefore, in some cases range-shifts may be limited by the capacity for novel migratory programmes to be transferred between generations, which can be genetically and socially mediated. Methods Here we used 50 years of North American Breeding Bird Survey and Audubon Christmas Bird Count data to test the prediction that breeding and/or non-breeding range-shifts are more prevalent among flocking migrants, which possess a capacity for rapid social transmission of novel migration routes. Results Across 122 North American bird species, social migration was a significant positive predictor for the magnitude of non-breeding centre of abundance (COA) shift within our study region (conterminous United States and Southern Canada). Across a subset of 81 species where age-structured flocking was determined, migrating in mixed-age flocks produced the greatest shifts and solo migrants the lowest. Flocking was not a significant predictor of breeding COA shifts, which were better explained by absolute population trends and migration distance. Conclusions Our results suggest that social grouping may play an important role in facilitating non-breeding distributional responses to climate change in migratory species. We highlight the need to gain a better understanding of migratory programme inheritance, and how this influences spatiotemporal population dynamics under environmental change.